Effectiveness of Social Skills Training in the High-risk Behaviors and Communication Skills of Secondary School Students - Hassan Khodaei; Ayat Fathi; Raheleh Alipour (Gonabad University of Medical Sciences, 2021)
Background: The present study aimed to determine the effectiveness of social skills training in high-risk behaviors and communication skills among secondary school students in Kaleybar City. Methods: This was a quasi-experimental study with a pre-test, post-test control group design. The statistical population of the study consisted of all the male high school students of Kaleybar City in the academic year of 2018-2019. First, two high schools were randomly selected from the districts of Kaleybar (East Azarbaijan province), one class was randomly selected from each school, and then, 40 students in the selected schools were randomly assigned into two groups: experimental (n=20) and control (n=20). The high-risk behaviors and communication skills scales were used for data collection. Descriptive statistics (mean and standard deviation) and covariance analysis were used to analyze the data at the significant level of 0.05. Results: The results showed that social skills training focused on high-risk behavior and its components (violence, smoking, drug use, alcohol consumption, and the opposite sex) and communication skills (feedback, listening, and verbal skills) positively affected the students, reduced risky behaviors, and increased communication skills (P<0.05). Conclusion: Paying attention to the social skills of students can crucially reduce their high-risk behaviors and enhance their communication skills.